PERBEDAAN HASIL BELAJAR MODEL KONVENSIONAL DAN MODEL PEMBELAJARAN GIVING QUESTION GETTING ANSWER SISWA MATA PELAJARAN AKIDAH AKHLAK KELAS X DI SMA AN-NUR BULULAWANG - Milatus Sholiha (VICRATINA, 2022)
The phenomenon in learning Akidah Akhlak teachers still use conventional learning with a lecture method where the teacher is only as a source of information so that students do play an pasife role in learning. With a learning model that is less effective, many students seem to be lazy, do not concern teachers in learning, many talk to their deskmates, and even in the classroom. Research type carried out is quantitative comparison with the design of " nonequivalent control Group Pretest-Posttest " using experimental groups with a control group and experiment group. The samples in this study were 24 students of class X IBB 3 and IPS 2with a non-probability sampling technique with purposive sampling type. Data analysis used was a paired sample test with the help of SPSS version 25. Based on the results of the study by conducting a Paired Sample Test with the provision that the sig value < 0.05, a sig value (2-tailed) of 0.000. So it can be concluded that a significant difference between the learning outcomes of the conventional model and the learning outcomes of the Giving Question Getting Answer learning model for class X students of Akidah Akhlak subjects at An-Nur Bululawang High School for the 2021/2022 academic year.Kata Kunci: Konvensional, Giving Question Getting Answer (GQGA), Hasil Belajar, Akidah Akhlak .